STUDYING THE TYPES AND THEIR COMPOSITION OF POLLUTANT MIXTURES CONTAINING COTTON SEEDS - Khuramova, Khadicha; Muradov, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Annotation: This article identifies the types of impurities in cotton and their composition. Technologies at cotton ginning enterprises have been studied. Impurity compounds cause a decrease in the quality indicators of seed cotton, and the processes of deterioration of cotton fiber have been studied. To obtain high-quality cotton fiber and seeds, impurities in seed cotton were experimentally determined.